#TimPakeTangan: Leveraging Electronic Word of Mouth for Payakumbuah’s Marketing Strategy on Twitter - Desna Aryana Pratiwi; Daffa Zaki Perdana; Rizky Wulan Ramadhani; Sabrina Rahma Utami; Bagus Dwi Bramantyo (Universitas Ahmad Dahlan, 2025)
Consumers increasingly make offline decisions based on online information, often relying on other users’ opinions shared on social media, with hashtags functioning as a form of electronic word of mouth (e-WOM) that amplifies brand messages and shapes audience engagement. This study aims to analyze how the hashtag #TimPakeTangan was utilized as e-WOM in Payakumbuah’s marketing strategy on Twitter. Payakumbuah, a Padang restaurant owned by Arief Muhammad, collaborated with Azizi from JKT48 to popularize the hashtag and enhance brand visibility. Drawing upon Social Proof Theory, this research employs a quantitative approach using Social Network Analysis (SNA) to examine online interactions and network dynamics. Data were collected from Twitter posts containing #TimPakeTangan between January 14 and 16, 2023, and analyzed using Netlytic and Gephi 0.9.7. The analysis identified 3,700 nodes and 5,042 edges, revealing @officialjkt48 as the central actor generating high engagement, while @jeon_sunghye and @a_zeejkt48 played active roles in disseminating the hashtag through replies, retweets, and original posts. The findings indicate that collaborations with influential social media figures significantly enhance e-WOM effectiveness and network reach. Theoretically, this research contributes to understanding how social proof operates within digital communication networks, while practically, it demonstrates how strategic hashtag campaigns and influencer collaborations can strengthen brand awareness and consumer engagement in social media marketing.